Vertical Ozone Concentration Profiles in the Arabian Gulf Region during Summer and Winter: Sensitivity of WRF-Chem to Planetary Boundary Layer Schemes - Christos Fountoukis (4722963) (2018)
Air quality in the Middle East is changing due to extensive land conversion, intense industrialization and rapid urbanization. In this study, we analyze data from an ozonesonde station operated in Doha, Qatar, by the Qatar Environment and Energy Research Institute (QEERI). Ozonesondes were launched weekly at 13:00 LT (10:00 UTC) during a summer month (August 2015) representative of extremely hot and humid atmospheric conditions and during a winter period (January–February 2016) representative of cool conditions in the area. Unlike similar studies in the region, this work focuses on the lower troposphere and combines high frequency vertical measurement data with the use of the Weather Research Forecasting model coupled with Chemistry (WRF-Chem). A sensitivity study was conducted to identify the most representative planetary boundary layer (PBL) parameterization. Although all three parameterizations that were examined produced similar results, the Yonsei University (YSU) PBL scheme was found to be statistically superior. Comparisons of model predictions against observations show high correlation coefficients and encouragingly low biases in all meteorological variables. During wintertime, ozone is well predicted overall (fractional bias = –0.1). Results from the summertime comparison are more challenging and point towards possible biases in the anthropogenic emission inventory of the Middle East, especially for rapidly-changing urban environments. Other Information Published in: Aerosol and Air Quality Research License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.4209/aaqr.2017.06.0194